Increasing Sales Turnover by Implementing Service Quality and Customer Satisfaction - Siti Rosyafah; Dien Ajeng Fauziah (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the company must strive to develop its business both in small and national businesses trying to survive and to develop in the future in the midst of the difficulty of the global economy, including government-owned companies, let alone the difficulty of competition between entrepreneurs in Indonesia. This study aims to determine the application of service quality and customer satisfaction in an effort to increase sales in Supermarkets. The object of this research was conducted at Sardo Supermarket Malang City with the method used was Qualitative Descriptive Method. The results of this study indicate that the quality of service and customer satisfaction at Sardo Supermarket shows that the quality of employees in serving customers is very good and customers feel very satisfied shopping at Sardo Supermarket. Although turnover every year experiences ups and downs Sardo Supermarket will not reduce the sense of service quality so that customers feel very satisfied to shop.